Anthelmintic effects of some medicinal plants on different life stages of Fasciola hepatica: Evidence on oxidative stress biomarkers, and DNA damage. - Mohaddeseh Allahyari; Farnaz Malekifard; Mohammad Yakhchali (Public Library of Science (PLoS), 2024)
Fasciolosis caused by Fasciola hepatica is a major public health and economic problem worldwide. Due to the lack of a successful vaccine and emerging resistance to the drug triclabendazole, alternative phytotherapeutic approaches are being investigated. This study investigated the in vitro anthelmintic activity of Lavender (Lavandula angustifolia) and carob (Ceratonia siliqua L.) essential oils (EOs) against F. hepatica. The in vitro study was based on an egg hatch assay (EHA), adult motility inhibition assays, DNA damage, reactive oxygen species (ROS) level along with several oxidative stress biomarkers including glutathione peroxidase (GSH), and glutathione-S-transferase (GST), superoxide dismutase (SOD) and malondialdehyde (MDA). To this end, different concentrations of L. angustifolia and C. siliqua EOs (1, 5, 10, 25 and 50 mg/mL) were used to assess anthelmintic effects on different life stages including egg, and adults of F. hepatica for 24 hrs. The results indicated that these EOs play a significant role as anthelminthics, and the effect was dependent on time and concentration. The in vitro treatment of F. hepatica worms with both L. angustifolia and C. siliqua EOs increased DNA damage, ROS production and induction of oxidative stress (decreased SOD, GST and GSH, and increased MDA), significantly compared to control. Therefore, it can be concluded that L. angustifolia and C. siliqua EOs have the potential to be used as novel agents for the control and treatment of F. hepatica infections. Further studies are required to investigate their pharmacological potential and effectiveness in vivo for the treatment of parasitic infections.